Image-Guided Spinal Surgery and Robotics in MIS: Where Are We Now? - Chiung Chyi Shen (Neurologico Spinale Medico Chirurgico, 2018)
Use of pedicle screws is widespread in spinal surgery for degenerative, traumatic, and oncological diseases. The conventional technique is based on the recognition of anatomic landmarks, preparation and palpation of cortices of the pedicle under control of an intraoperative C-arm (iC-arm) fluoroscopy. With these conventional methods, the median pedicle screw accuracy ranges from 86.7% to 93.8%, even if perforation rates range from 21.1% to 39.8%. The development of novel intraoperative navigational techniques, commonly referred to as image-guided surgery (IGS), provide simultaneous and multiplanar views of spinal anatomy. IGS technology can increase the accuracy of spinal instrumentation procedures and improve patient safety. These systems, such as fluoroscopy-based image guidance ("virtual fluoroscopy") and computed tomography (CT)-based computer-guidance systems, have sensibly minimized risk of pedicle screw misplacement, with overall perforation rates ranging from between 14.3% and 9.3%, respectively. "Virtual fluoroscopy" allows simultaneous two-dimensional (2D) guidance in multiple planes, but does not provide any axial images; quality of images is directly dependent on the resolution of the acquired fluoroscopic projections. Furthermore, computer-assisted surgical navigation systems decrease the reliance on intraoperative imaging, thus reducing the use of intraprocedure ionizing radiation. The major limitation of this technique is related to the variation of the position of the patient from the preoperative CT scan, usually obtained before surgery in a supine position, and the operative position (prone). The next technological evolution is the use of an intraoperative CT (iCT) scan, which would allow us to solve the position-dependent changes, granting a higher accuracy in the navigation system. Image